Monitoring the agri-food system in Myanmar: Rice millers – March 2023 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
In March 2023, we interviewed more than 430 active rice millers to assess business disruptions and price changes at the midstream of Myanmar’s most important agricultural value chain. Key findings  High fuel costs and electricity supply remain the most commonly reported disruptions in March 2023, with medium/ large modern mills facing more issues related to transport costs, electricity supply, and transport restrictions.  Among the disruptions, electricity access is the most significant disruption for both medium/large-scale mills and small/micro mills, followed by fuel costs and fuel access.  Smaller mills experienced declines in throughput, while larger mills maintained similar monthly throughput and decreased paddy storage compared to the previous year. Larger mills were less willing to provide credit to farmers, and there was an increase in byproduct sales for smaller mills.  Wages paid by mills increased by about 18 percent, working capital requirements to buy paddy rose significantly for both larger and smaller mills, and milling commission fees increased for both mill types compared to last year.  Paddy and rice prices for Emata and Pawsan varieties have significantly increased in March 2023, surpassing prices from March 2021 and 2022 due to currency devaluation and a slight increase in global rice prices. Milling margins have also increased compared to previous years. Despite the price hikes, millers are not extracting a disproportionate share of rice prices, and the prices of main byproducts, like broken rice and rice bran, have remained healthy, presenting positive prospects for mill profit margins.